Tahlil al-Akhtha’ al-Shautiyyah li al-Kalimat al-Thayyibat fi Hayat al-Muslimin (Dirasah Tahliliyyah Shautiyyah) - Misbahul Munir (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
This research aims to explain the sound error al-kalimāh aṭ-ṭayyibah, vowels and consonants. The research conducted at UIN Yogyakarta. Sources of data obtained from Arabic Linguistic Studies of Post Graduate Students in UIN Yogyakarta. The method used is descriptive-qualitative with case study approach. Data collection of this research used interviewing, taking notes, and recordings. This research shows that the mistakes found in vowels; either short, long, and double vowel sound. Fatḥah(َ) sounds /a/ becomes /o./ Ḍammah(ُ) sounds /u/ becomes /o/, /ū/, dan sukūn/ْ./ Kasrah(ِ) sounds /i/ becomes /e./ Syaddah(ّ) which read double will be not double. Fatḥah(َ) which followed alif(ا), it sounds /ā/ and becomes /a./ Fatḥah(َ) which followed alif(ا) dan tilda( ) above it, it sounds /ā/ and becomes /a./ Fatḥah(َ) which followed wawu sukūn(وْ), sounds /au/ and becomes /ao./ Fatḥah(َ) which followed ya’ sukūn(يْ), sounds /ai/ and becomes /ei./ The error sound of the consonants, consonant phoneme sound ع/‘/ becomes ا/’/, ح/ḥ/ becomes ه/h/ and ك/k/, ظ/ẓ/ becomes ز/z/ and ج/j/, ش/sy/ becomes س/s/, ق/q/ becomes ك/k/, ذ/ż/ becomes ظ/ẓ/ and د/d/, ت/t/ becomes ط/ṭ./ The sound of the vowels and consonants errors occur due to there is link between language with speakers.